Schriftleitung in wechselhafter Zeit: die "Zeitschrift für katholische Theologie" unter P. H. B. Meyer SJ (1924-2002) - Neufeld, Karl H. (Zeitschrift für katholische Theologie, 2002)
P. H. B. Meyer directed this review for nearly 35 years after the Second Vatican Council. His death gives the opportunity to look back on the philosophical and theological discussion of this period in so far as it is documented in the "Zeitschrift für Katholische Theologie". The evolution on this level was very great not only in themes and topics but also in the role of stamped contributions. This is the background for new perspectives and possibilities of a review destined to continue a long line of interventions, but also to answer deeper questions of actual christian and theological life.